Extractive metallurgy of copper - Schlesinger, Mark E.; King, Matthew J.; Sole, Kathryn C.; Davenport, W. G. (Elsevier, 2011)
"This multi-author new edition revises and updates the classic reference by William G. Davenport et al (winner of, among other awards, the 2003 AIME Mineral Industry Educator of the Year Award "for inspiring students in the pursuit of clarity"), providing fully updated coverage of the copper production process, encompassing topics as diverse as environmental technology for wind and solar energy transmission, treatment of waste by-products, and recycling of electronic scrap for potential alternative technology implementation. The authors examine industrially grounded treatments of process fundamentals and the beneficiation of raw materials, smelting and converting, hydrometallurgical processes, and refining technology for a mine-to-market perspective - from primary and secondary raw materials extraction to shipping of rod or billet to customers. The modern coverage of the work includes bath smelting processes such as Ausmelt and Isasmelt, which have become state-of-the-art in sulfide concentrate smelting and converting."--Publisher's description.